Synthesis of Copper Nanocluster and Its Application in Pollutant Analysis - Yan Xue (MDPI AG, 2021)
Copper nanoclusters (Cu NCs) with their inherent optical and chemical advantages have gained increasing attention as a kind of novel material that possesses great potential, primarily in the use of contaminants sensing and bio-imaging. With a focus on environmental safety, this article comprehensively reviews the recent advances of Cu NCs in the application of various contaminants, including pesticide residues, heavy metal ions, sulfide ions and nitroaromatics. The common preparation methods and sensing mechanisms are summarized. The typical high-quality sensing probes based on Cu NCs towards various target contaminants are presented; additionally, the challenges and future perspectives in the development and application of Cu NCs in monitoring and analyzing environmental pollutants are discussed.